2016
DOI: 10.1590/1806-9282.62.02.151
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutants and hospital admission due to pneumonia in children: a time series analysis

Abstract: Objective: The aim of this study was to estimate the association between exposure to air pollutants and hospitalization for pneumonia among children in a medium-sized city located in the sugar cane plantation region of São Paulo State. Methods: An ecological time-series study was conducted with daily data of hospitalization for pneumonia including children aged 10 years or younger living in Araraquara, state of São Paulo, from January 1 st , 2010, to November 30 th , 2012. To estimate the association between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
(32 reference statements)
2
15
0
2
Order By: Relevance
“…Souza et al found a strong association between hospitalization and PM 10 and NO 2 . The percentage increase in relative risk was 15% to PM 10 in Lag 0 and 7% in Lag 1 for NO 2 (Souza and Nascimento, 2016). Patto et al reported that a rise of 10 µg/m 3 in the concentration of PM 2.5 leads to significant increase between 25 ppt and 28 ppt in the risk of hospitalization due to pneumonia among children 4 and 5 days after exposure (Patto et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Souza et al found a strong association between hospitalization and PM 10 and NO 2 . The percentage increase in relative risk was 15% to PM 10 in Lag 0 and 7% in Lag 1 for NO 2 (Souza and Nascimento, 2016). Patto et al reported that a rise of 10 µg/m 3 in the concentration of PM 2.5 leads to significant increase between 25 ppt and 28 ppt in the risk of hospitalization due to pneumonia among children 4 and 5 days after exposure (Patto et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…These reports suggest that primary traffic pollutants, ozone, and fine and coarse particulate air pollution exacerbate upper and lower respiratory infections and the disease burden of respiratory infections such as pneumonia, bronchiolitis, bronchitis, and upper respiratory infection in early life (Darrow et al, 2014;Anenberg et al, 2012;Wang et al, 2013;Kesavachandran et al, 2013). Particulate matter originated from other sources, such as burning of fossil fuels and biomass, is also associated with increased incidence of pneumonia and increased symptoms and respiratory disease (Souza and Nascimento, 2016). Experimental and epidemiologic studies have demonstrated that the severity of pneumonia has positive associations with exposure of air pollutants (Harrod et al, 2003;Mikerov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in high-income developed countries, the estimated loss of YLDs due to respiratory diseases was much lower than that in low-income developed countries, regardless of sex or age [21]. This may be due to air pollution, which is positively associated with the admission of respiratory patients in developing countries among different age groups; this association is especially strong in vulnerable groups (children and elderly individuals) [22][23][24]. However, the fact that community health centre visits were frequently for acute upper respiratory tract infections was ignored in terms of public healthcare resource allocation [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Araraquara, SP, which is a major producer of sugar and alcohol and is located about 200 km from São José do Rio Preto, exposure to PM 10 was associated with hospitalizations for pneumonia in children, with concentrations of this pollutant (35.7 µg/ m 3 ) similar to the adjusted concentrations found in São José do Rio Preto (31.6 µg/m 3 ). 19 Exposures to PM 2.5 were associated with hospitalizations due to bronchiolitis in a study by Sheffield et al 20 conducted between 1999 and 2007 based on the National Inpatient Sample, the largest database that evaluates hospitalization costs for bronchiolitis in the United States. In this study, the authors identified nearly 48,000 hospitalizations for bronchiolitis associated with exposure to PM 2.5 and estimated a cost reduction of approximately US$ 15 million per year, resulting from the decrease in the concentrations of this pollutant.…”
Section: Discussionmentioning
confidence: 99%